X-7=13

move -7 to the right side of the equation, change the sign from negative to positive when you move it

x-7+7=13+7

x=13+7

x=20

**Answer:**

C. Indirect Proof

**Step-by-step explanation:**

There are two methods of indirect proof: proof of the contrapositive and proof by contradiction.

Bruh just google it, get an immediate answer there

**Answer:**

<h2>C. y + 9 = -4(x - 4)</h2>

**Step-by-step explanation:**

The point-slope form of an equation of a line:

<em>**m**</em><em> - slope</em>

<em>**(x₁, y₁)**</em><em> - point on a line</em>

<em />

We have the slope <em>**m = -4**</em>, and the point <em>**(4, -9)**</em>.

Substitute: